A critical kinase cascade in neurological disorders: PI3K, Akt and mTOR. (November 2012) - Chong, Zhao Zhong; Shang, Yan Chen; Wang, Shaohui; Maiese, Kenneth
Neurodegenerative disorders lead to disability and death in a significant proportion of the world's population. However, many disorders of the nervous system remain with limited effective treatments. Kinase pathways in the nervous system that involve PI3K, Akt and mTOR offer exciting prospects for the understanding of neurodegenerative pathways and the development of new avenues of treatment. PI3K, Akt and mTOR pathways are vital cellular components that determine cell fate during acute and chronic disorders, such as Huntington's disease, Alzheimer's disease, Parkinson's disease, epilepsy, stroke and trauma. However, the elaborate relationship among these kinases and the variable control of apoptosis and autophagy can lead to unanticipated biological and clinical outcomes. Crucial for the successful translation of PI3K, Akt and mTOR into robust and safe clinical strategies will be the further elucidation of the complex roles that these kinase pathways hold in the nervous system.